Rifampin resistance and diabetes mellitus in a cross-sectional study of adult patients in rural South India. Issue 1 (December 2015) - Mehta, Saurabh; Yu, Elaine; Ahamed, Syed; Bonam, Wesley; Kenneth, John
Abstract Background Despite increasing reports of the linkage between diabetes and tuberculosis (TB), there is limited information regarding diabetes and TB drug resistance. Methods In this cross-sectional study, sputum and blood samples were collected from 304 adult patients in rural Andhra Pradesh. Rifampin resistance was assessed by Xpert MTB/RIF (Xpert), and diabetes status was based on self-report. Additionally, samples were assayed by acid-fast bacilli sputum smear microscopy (AFB) and QuantiFERON-TB Gold In-Tube (QFT-G), in order to compare relative diagnostic performances. Results Among patients with confirmed TB (n = 194), diabetes was associated with 3.0-fold higher risk of rifampin resistance (95 % CI 1.3–6.7). Considering Xpert MTB/RIF the gold standard, AFB had lower sensitivity (72.2 vs. 82.5 %) and higher specificity (96.4 vs. 37.0 %) compared to QFT-G for diagnosing TB. Conclusions The increased risk of rifampin resistance in patients with diabetes highlights the need for integrated diabetes surveillance in TB programs, particularly in settings undergoing the epidemiological transition.